Personal finance for dummies - Tyson, Eric (Eric Kevin) (--For dummies., 2010)
Discusses financial health, debt management, and taxes; offers advice on investing in stocks, retirement accounts, and real estate; and explores insurance, planning for life changes and children's education, and hiring financial advisors.